A wheat NAC interacts with an orphan protein and enhances resistance to Fusarium head blight disease. Issue 10 (29th April 2019) - Perochon, Alexandre; Kahla, Amal; Vranić, Monika; Jia, Jianguang; Malla, Keshav B.; Craze, Melanie; Wallington, Emma; Doohan, Fiona M.
Summary: Taxonomically‐restricted orphan genes play an important role in environmental adaptation, as recently demonstrated by the fact that the Pooideae ‐specific orphan TaFROG ( Triticum aestivum Fusarium Resistance Orphan Gene) enhanced wheat resistance to the economically devastating Fusarium head blight (FHB) disease. Like most orphan genes, little is known about the cellular function of the encoded protein TaFROG, other than it interacts with the central stress regulator TaSnRK1α. Here, we functionally characterized a wheat ( T. aestivum ) NAC–like transcription factor TaNACL‐D1 that interacts with TaFROG and investigated its' role in FHB using studies to assess motif analyses, yeast transactivation, protein‐protein interaction, gene expression and the disease response of wheat lines overexpressing TaNACL‐D1 . TaNACL‐D1 is a Poaceae ‐divergent NAC transcription factor that encodes a Triticeae ‐specific protein C‐terminal region with transcriptional activity and a nuclear localisation signal. The TaNACL‐D1/TaFROG interaction was detected in yeast and confirmed in planta, within the nucleus. Analysis of multi‐protein interactions indicated that TaFROG could form simultaneously distinct protein complexes with TaNACL‐D1 and TaSnRK1α in planta . TaNACL‐D1 and TaFROG are co‐expressed as an early response to both the causal fungal agent of FHB, Fusarium graminearum and its virulence factor deoxynivalenol (DON). Wheat lines overexpressing TaNACL‐D1 were more resistant to FHB disease than wild type plants. Thus, we conclude that the orphan protein TaFROG interacts with TaNACL‐D1, a NAC transcription factor that forms part of the disease response evolved within the Triticeae .